Pengaruh Jumlah Tanaman Per Lubang Terhadap Vigor Benih Tiga Varietas Sorgum (Sorghum bicolor [L].Moench) Dengan Metode Pengusangan Cepat (MPC) - Purnamasari, Lidya; Pramono, Eko; Kamal, M. (Politeknik Negeri Lampung., 2015)
The aim of this study is to determine the effect of the number of plants per hole on seed vigor of all sorghum varieties. Experiment is prepared by treatment with randomized block design (RAK) and repeated three times to do to achieve that goal. The first factor is the number of plants per hole that is 1 plant / hole (p1), 2 plants / hole (p2), 3 plants / holes (p3), and 4 plants / hole (p4). The second factor is the variety Numbu (g1), Keller (g2), and Wray (g3). The seed that had been harvested from each of the combination treatments in the test vigornya through germination test method Rolled Paper Test (UKD). Prior to germinate, seeds treated quickly with imbibition pengusangan on rice paper damp ethanol 8%. The results showed that the population of one plant per hole produces seeds with higher vigor than those harvested from other populations. Numbu varieties produce seeds with higher vigor than varieties Keller and Wray especially on untreated seed pengusangan quickly. Population 1 plant per hole produces the best vigor compared with a population of 2, 3 and 4 plants per hole on the three varieties of sorghum seed. Keywords: seeds, planting amount per hole, metode pemngusangan cepat, sorghum, vigor